CLASSIFICATION OF STUNTING IN CHILDREN UNDER FIVE YEARS IN PADANG CITY USING SUPPORT VECTOR MACHINE - Rahmi, Izzati; Susanti, Mega; Yozza, Hazmira; Wulandari, Frilianda (PATTIMURA UNIVERSITY, 2022)
Stunting is a nutritional problem in children characterized by the child’s height that is less than twice the standard deviation of the median standard from children growth that has been determined by the WHO. Stunting is influenced by many factors. If the conditional of these factors are known, it can be expected earlier whether a child is stunted or not. In this study, the prediction of stunting was carried out using the Support Vector Machine (SVM) classification method. SVM is a method to find the best hyperplane that can be used to separate two or more classes. In this study, the parameter of the SVM model that must be determined is the cost value and gamma. Based on the result of research using parameters cost=10 and gamma=5, the estimation result of the classification with 100% accuracy can be obtained.